2020
DOI: 10.3389/fmars.2020.00188
|View full text |Cite
|
Sign up to set email alerts
|

Annual Bands in Vertebrae Validated by Bomb Radiocarbon Assays Provide Estimates of Age and Growth of Whale Sharks

Abstract: Conservation and management strategies for endangered and threatened species require accurate estimates of demographic parameters such as age and growth. The whale shark, Rhincodon typus, is the largest fish in the world and is highly valued in the eco-tourism sector. Despite conservation concerns and advances in our understanding of their life history, basic demographic parameters for growth, longevity and mortality are of questionable accuracy; previous growth studies could not agree whether the vertebral gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Using a back-calculation approach on vertebral increments, Wintner (2000) demonstrated that the earliest growth trajectories may be J-shaped, implying a slow initial start that results in a growth profile that conforms better to a logistic rather than von Bertalanffy model. Indeed, use of a logistic model in Ong et al (2020) produced estimates of asymptotic length (10.7 m) more similar to our estimates for males, and a slower initial growth rate in general might account for the differences in predicted age-specific growth rates between our study and others. Although there are very few published observations of growth rates for whale shark pups, a full-term embryo (sex not provided) raised for 120 days in Taiwan (taken from a commercially harvested mother; Chang et al, 1997) and a male embryo raised for 1157 days in the Okinawa Churaumi Aquarium (Nishida, 2001) displayed linear growth trajectories in excess of rates predicted even by the present study (Figure 4).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Using a back-calculation approach on vertebral increments, Wintner (2000) demonstrated that the earliest growth trajectories may be J-shaped, implying a slow initial start that results in a growth profile that conforms better to a logistic rather than von Bertalanffy model. Indeed, use of a logistic model in Ong et al (2020) produced estimates of asymptotic length (10.7 m) more similar to our estimates for males, and a slower initial growth rate in general might account for the differences in predicted age-specific growth rates between our study and others. Although there are very few published observations of growth rates for whale shark pups, a full-term embryo (sex not provided) raised for 120 days in Taiwan (taken from a commercially harvested mother; Chang et al, 1997) and a male embryo raised for 1157 days in the Okinawa Churaumi Aquarium (Nishida, 2001) displayed linear growth trajectories in excess of rates predicted even by the present study (Figure 4).…”
Section: Discussionsupporting
confidence: 76%
“…Wintner (2000) estimated a size (15 m) that was closer to our estimates for females when theoretical data points were added to the calculation of the VBGM, but a size of almost 20 m when the relationship was unconstrained by these points. Similarly, Ong et al (2020) predicted asymptotic sizes of 22 m for whale sharks off the coast of Taiwan using a von Bertalanffy model Taiwan (Hsu et al, 2014) Annual rings Size ranges of whale sharks used in each study are displayed in the Supplementary Material (Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation may be particularly problematic for older individuals because not all growth bands may be deposited in vertebrae past a certain age (Francis et al 2007;Passerotti et al 2014;Harry 2017). Nevertheless, where well-demonstrated cases of annual band deposition are known (Goldman et al 2012, and references therein;Ong et al 2020), the relationship of growth bands to time or age can still be broadly correlated (Natanson and Deacy 2019), and remains a widely used life-history assessment technique for diverse modern elasmobranchs (e.g. Ong et al 2020;Rolim et al 2020).…”
Section: Introductionmentioning
confidence: 99%